Do Nonsuicidal Severely Depressed Individuals with Diabetes Profit from Internet-Based Guided Self-Help? Secondary Analyses of a Pragmatic Randomized Trial. (14th May 2019) - Schlicker, Sandra; Weisel, Kiona K.; Buntrock, Claudia; Berking, Matthias; Nobis, Stephanie; Lehr, Dirk; Baumeister, Harald; Snoek, Frank J.; Riper, Heleen; Ebert, David D.
Abstract : Introduction . Diabetes mellitus type 1 and type 2 are linked to higher prevalence and occurrences of depression. Internet-based depression- and diabetes-specific cognitive behavioral therapies (CBT) can be effective in reducing depressive symptom severity and diabetes-related emotional distress. The aim of the study was to test whether disease-specific severity indicators moderate the treatment outcome in a 6-week minimally guided web-based self-help intervention on depression and diabetes (GET.ON Mood Enhancer Diabetes (GET.ON M.E.D.)) and to determine its effectiveness in a nonsuicidal severely depressed subgroup. Methods . Randomized controlled trial- (RCT-) based data (N = 253 ) comparing GET.ON M.E.D. to an online psychoeducation control group was used to test disease-specific severity indicators as predictors/moderators of a treatment outcome. Changes in depressive symptom severity and treatment response were examined in a nonsuicidal severely depressed subgroup (CES − D > 40 ;N = 40 ). Results . Major depressive disorder diagnosis at the baseline (p prf 6 = 0.01 ), higher levels of depression (Beck Depression Inventory II;p prpo = 0.00 ;p prf 6 = 0.00 ), and lower HbA1c (p prpo = 0.04 ) predicted changes in depressive symptoms. No severity indicator moderated the treatment outcome. Severely depressed participants in the intervention group showed a significantly greater reduction in depressive symptom severity (d prpo = 2.17, 95% Confidence Interval (CI): 1.39-2.96) than the control condition (d prpo = 0.92 ; 95% CI: 0.001-1.83), with a between-group effect size ofd prpo = 1.05 (95% CI: 0.11-1.98). Treatment response was seen in significantly more participants in the intervention (4/20; 20%) compared to the control group (0/20, 0%;χ 2 2 N = 40 = 4.44 ;p < 0.02 ). At the 6-month follow-up, effects were maintained for depressive symptom reduction (d pr 6 f = 0.71 ; 95% CI: 0.19-1.61) but not treatment response. Conclusion . Disease-specific severity indicators were not related to a differential effectiveness of guided self-help for depression and diabetes. Clinical meaningful effects were observed in nonsuicidal severely depressed individuals, who do not need to be excluded from web-based guided self-help. However, participants should be closely monitored and referred to other treatment modalities in case of nonresponse.